Pests of cabbage (Brassica oleracea L Var.capitata) and Cauliflower (Brassica Oleracea L.var.botrytis) and their management - G.B.Ravi (Department of Agricultural Entomology, College of Agriculture, 2013)
Investigations on “Pests of cabbage (Brassica oleracea L. var. capitata) and cauliflower (Brassica oleracea L. var. botrytis) and their management” were carried out at College of Agriculture, Vellayani during 2011-13. The main objective of the work was to identify the pests and natural enemies associated with cabbage and cauliflower and to evolve pest management strategies. Analysis of pest fauna in cabbage and cauliflower revealed that the crops were attacked by eighteen pest species. The occurrence of pierid butterfly Appias lyncida Cramer on cruciferous crops is reported for the first time. The key pest affecting the crop grown in plains was the cut worm Spodptera litura (Fabricius) and in the hilly tracts it was Plutella xylostella (Linnaeus). Damage caused by S. litura was 30% in cabbage and cauliflower and that by P. xylostella was 38% to heads and 26 % to curds. Two coccinellid predators Chilomenes sexmaculata Fabr. and Coccinella transversallis Fabricius and the syrphid, Ischiodon scutellaris Fabricius were identified from the colonies of aphid, Lipaphis erysimi (Kaltenbach). One parasitoid, Protapanteles sp. was identified from larvae of Plusia signata Fab. Further investigations were focused on S. litura, the major pest in plains. Detailed studies on biology of the pest revealed high fecundity and survival percentage of all the life satges (80 -100), favouring high feeding potential and rapid buildup of population. S. litura incidence in cabbage reached the peak level at head fill stage (13WAP) in cabbage and in cauliflower the peak was observed at curd development stage (12WAP). Correlation studies of the population with weather parameters revealed that the pest and abiotic factors did not show any consistent association. The relative importance of different abiotic factors that acted upon the pest varied during the period. Preliminary screening of entomopathogens, botanicals and new generation insecticides undertaken under laboratory conditions revealed that, GE 2%, NSKE 5 %, SFE 10 % and the synthetic insecticides, indoxacarb 0.008%, and cypermethrin 0.03% were equally effective as the treated check, malathion 0.15%. Field studies conducted using the above selected treatments revealed that the reduction in population of S. litura was maximum with indoxacarb 0.008%, followed by cypermethrin 0.03% and the treated check, malathion 0.15%. Among the botanicals GE 2% was found to be the most effective in reducing the population, followed by 5% NSKE. Management of S. litura had a significant effect on yield of cabbage and cauliflower. Indoxacarb 0.008% resulted in 29.37 per cent increase in net yield of cabbage. The effect of cypermethrin 0.03%, malathion 0.15%, GE 2% and NSKE 5% were also noteworthy in increasing the yield by 23.07 to 28.35 per cent. In cauliflower, there was a yield increase of 53.38 to 60.07 per cent, indoxacarb 0.008%, cypermethrin 0.03%, malathion 0.15%, 10%, NSKE 5% and GE 2%. Samples analysed for residues, at the time of harvest revealed that the mean residue of indoxacarb 0.008%, and cypermethrin 0.03% were below detectable limit. From the above study it is concluded that, the key pest of cabbage and cauliflower grown in hilly tracts was DBM and that in the plains was S. litura. S. litura can effectively be managed by adopting management strategies in the true leaf, cupping and early head formation or curd initiation stages of these crops. Indoxacarb 0.008% and cypermethrin 0.03%, can safely be used as there was no residual problems. Considering the ecological and economic factors, spraying 2 % GE or 5 % NSKE is the safer.